A Retrospective Study in Trans Individuals Undergoing Gender Affirming Testosterone Treatment: Can Changes in Prolactin Counteract the Negative Effects on the Lipid Profile? - Jojo Steininger; Katalin Widmann; Ulrike Kaufmann; Marlene Hager; Rodrig Marculescu; Robert Krysiak; Johannes Ott (Biomedicines)
Background/Objectives: Gender-affirming hormone therapy (GAHT) is known to influence the lipid profiles of trans men and transmasculine individuals. Recent data show that moderate prolactin (PRL) elevations might exert beneficial metabolic effects (“HomeoFIT-PRL model”). The aim of this study is to investigate changes in PRL levels and possible associations between PRL and lipid profiles in this population after a year of GAHT. Methods: In a retrospective cohort study, 97 participants, who received GAHT with testosterone, were included. Blood lipids, PRL, and sex steroid hormone levels were evaluated prior to and at 10–14 months after treatment started. Results: The difference in PRL levels between baseline and follow-up was significant (p = 0.007) with a median difference of +2.3 ng/mL. Concerning blood lipids, the decline in high-density lipoprotein cholesterol (HDL-C) reached statistical significance (median 56 mg/dL versus 50 mg/dL; p < 0.001), and low-density lipoprotein cholesterol (LDL-C) and triglyceride levels increased (p = 0.023 and p = 0.045, respectively). Individuals with a PRL > 25 ng/mL at follow-up (n = 20, 20.6%) revealed increases in total cholesterol and LDL-C significantly less often. Overall, participants frequently displayed unfavorable changes in their lipid profile after 10–14 months of GAHT, as well as a slight but significant increase in PRL. About 20% of patients showed mild-to-moderate hyperprolactinemia (PRL > 25 ng/mL). However, such changes were associated with potentially beneficial dynamics in the lipid profile, at least for triglycerides. Conclusions: These findings seem in line with the HomeoFIT-PRL model suggesting that moderate elevations in PRL levels might exert beneficial metabolic effects. Increases in PRL after testosterone were common.